EVALUATION OF THE QUALITY OF MEAT AND PROCESSED MEAT PRODUCTS FROM KUMBASARI TRADITIONAL MARKET AND COKROAMINOTO MARKET, DENPASAR CITY, BALI - Mahaputra, I Made; Bolla, Nelci Elisabeth; Roby, I Made; Juniartini, Wieke Sri; Nazara, Agustina Lesmauli; Swacita, Ida Bagus Ngurah (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023DO - 10.24843/bulvet.2023.v15.i02.p09, 2023)
Meat quality security is absolutely necessary to ensure that the public as consumers get meat that is safe, healthy, whole, and halal for consumption. This test aims to evaluate the quality of meat and processed meat products in terms of subjective and objective tests. The samples used in this test were beef, pork, chicken, and fish as well as processed meat products in the form of meatballs and sausages from chicken, beef, pork, and fish from Kumbasari Traditional Market and Cokroaminoto Market, Denpasar City, Bali. All meat samples were tested for quality subjectively including color, odor, consistency and texture, state of the weave binder, marbledness of meat and objectively covering pH, water holding capacity, moisture content, microbial contamination. In processed meat products, subjective tests are carried out only for color, aroma, consistency, texture, taste and objective tests with pH checks. The results of tests on meat and processed meat products that have been carried out both subjectively and objectively show that beef, pork, chicken and meatballs and beef, pork, chicken and fish sausages have good quality. However, in testing the fish meat has a soft texture, a fishy smell mixed with a foul odor (no smell of fresh blood) and microbial contamination that exceeds the maximum limit. It can be concluded that beef, pork, chicken, processed meat products and processed fish products from Kumbasari Market and Cokroaminoto Market are suitable for consumption. Meanwhile, the fish meat from the Kumbasari Market and Cokroaminoto Market that were tested were not suitable for consumption.